TRADITIONAL PRODUCTS AND ORGANIC FARMING – THE REVIVAL CHANCE OF THE ROUMANIAN VILLAGE - Nedelcu, Monica (Economics of Agriculture, 2012)
Consumers in the European Union are increasingly interested not only in food quality but also in the origin and methods of food production. The diversity expresses the richness of Europe and all traditional and organic products that meet quality standards set by the European Union should be recognized and protected. The protection and registration of Romanian traditional products as well as the certification of organic foods will ensure a fair competition between manufacturers and product credibility in the eyes of consumers.